Assessing stereophotoclinometry by modeling a physical wall representing asteroid Bennu. (15th November 2020) - Craft, K.L.; Barnouin, O.S.; Gaskell, R.; Palmer, E.; Weirich, J.; Perry, M.; Bierhaus, B.; Norman, C.; Huish, D.; Olds, R.; Daly, M.G.; Lorenz, D.; et al.
Abstract: The Origins, Spectral Interpretation, Resource Identification, and Security–Regolith Explorer (OSIRIS-REx) mission is characterizing the surface and orbital environment of the primitive asteroid (101955) Bennu to enable the collection and return of pristine samples of carbonaceous material. The Altimetry Working Group (AltWG) generates digital terrain models (DTMs) that are essential for assessing the sampleability and science value of potential sample sites. The AltWG uses stereophotoclinometry (SPC) to generate these DTMs from images collected by the OSIRIS-REx Camera Suite. We built and evaluated an SPC-derived DTM by performing a flight-like test, using images (0.4–3 ​cm per pixel) of a physical test wall constructed to simulate a 3 ​m ​× ​3 ​m portion of Bennu's surface. We built the DTM using images acquired under similar lighting conditions to those planned for the OSIRIS-REx mission and processed them using flight-like SPC procedures. The results were compared to measurements of the wall obtained using a laser altimeter. We found maximum height differences between the SPC-derived model and the altimetric data of −2.6 and 3.4 ​cm (or 13–17% of the dynamic range of the heights across the wall), specifically around large surface rocks. For the majority of the SPC-derived model, differences are less than ​± ​0.5 ​cm (<2.5% of the dynamic range of the heights across the wall) or ~1.5× the images' best pixel scale of 0.4 ​cm. In the spatial frequency domain, spectral correlation and coherency assessments comparing the SPC-derived model and the altimetric data show that the SPC-generated DTMs are an excellent product from wavelengths of ~3 ​m down to shorter wavelengths of ~0.1 ​m. Cross-correlation assessment of images rendered from the SPC-derived model vs. images of the test wall further show that our models accurately reproduce the combined albedo and surface shape, with cross-correlation scores >0.65. Graphical abstract: Image 1 Highlights: Demonstrated that stereophotoclinometry (SPC)-derived digital terrain model (DTM) represents Bennu surface well. The OSIRIS-REx mission can rely on SPC models for understanding the topography of Bennu. The majority of SPC model vs. altimetric data height differences were <2.5% of the dynamic range. SPC-DTMs are excellent for wavelengths (ground sample distances) ~3 ​m–~0.03 ​m. SPC accurately reproduces the combined albedo and surface shape, adequate for navigation.